Michael Moore, an American Populist? - Jensen, Mikkel (Anafora, 2023)
This article contextualizes the films of Michael Moore in the tradition of American populism. Extending in particular from historian Thomas Frank’s argument in People without Power that populism can usefully be understood as a particular American tradition of leftism, the article traces how three of Moore’s films—Roger & Me (1989), Sicko (2007), and Capitalism: A Love Story (2009)—articulate political concerns that overlap with the political beliefs of American populism. The article also explores some of the populist elements in Moore’s style and argues that there is good reason to see Michael Moore as a twenty-first-century American populist but that any attempt to do so must remain clear about the definitions of populism used to make this contextualist argument.